Temperature-induced microstructural changes in shells of laboratory-grown Arctica islandica (Bivalvia) - Höche, N.; Walliser, E.O.; de Winter, N.J.; Witbaard, R.; Schöne, B.R. (PLOS ONE, 2021)
Bivalve shells are increasingly used as archives for high-resolution paleoclimate analyses. However, there is still an urgent need for quantitative temperature proxies that work without knowledge of the water chemistry–as is required for δ 18 O-based paleothermometry–and can better withstand diagenetic overprint. Recently, microstructural properties have been identified as a potential candidate fulfilling these requirements. So far, only few different microstructure categories (nacreous, prismatic and crossed-lamellar) of some short-lived species have been studied in detail, and in all such studies, the size and/or shape of individual biomineral units was found to increase with water temperature. Here, we explore whether the same applies to properties of the crossed-acicular microstructure in the hinge plate of Arctica islandica , the microstructurally most uniform shell portion in this species. In order to focus solely on the effect of temperature on microstructural properties, this study uses bivalves that grew their shells under controlled temperature conditions (1, 3, 6, 9, 12 and 15°C) in the laboratory. With increasing temperature, the size of the largest individual biomineral units and the relative proportion of shell occupied by the crystalline phase increased. The size of the largest pores, a specific microstructural feature of A . islandica , whose potential role in biomineralization is discussed here, increased exponentially with culturing temperature. This study employs scanning electron microscopy in combination with automated image processing software, including an innovative machine learning–based image segmentation method. The new method greatly facilitates the recognition of microstructural entities and enables a faster and more reliable microstructural analysis than previously used techniques. Results of this study establish the new microstructural temperature proxy in the crossed-acicular microstructures of A . islandica and point to an overarching control mechanism of temperature on the micrometer-scale architecture of bivalve shells across species boundaries.